EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE TEAM GAME TOURNAMENT TERHADAP HASIL BELAJAR SISWA DENGAN BANTUAN MEDIA EDUCAPLAY - Dewi, Ellya Kusna Aura; Azizah, Devi Nur; Ratnasari, Diah Ayu; Khasanah, Elok Rosyidatul; Faqih, Fauziah Nur; Khumairoh, Fidyah Nur; Hanafi, Yusuf; Kustia, Cahyaning Pininta (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The objective of this study is to determine the effectiveness of the cooperative learning model of the TGT (Teams Games Tournament) type assisted by Educaplay media in improving the learning outcomes of Class IX.8 students at SMPN 3 Malang. This research is based on the need to select a more suitable learning model for theoretical materials, such as the topic "Impacts of Social Media," which is often delivered through conventional methods that do not actively engage students. This lack of engagement can lead to decreased motivation and lower academic achievement. This study employed a pre-experimental method with a one-group pretest-posttest design. The research sample consists of 30 students from Class IX.8 at SMPN 3 Malang. The collected data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, and N-Gain test. The normality test results showed that both the pretest (0.125) and posttest (0.086) scores were normally distributed. The t-test result was 0.000 (< 0.05), indicating that the TGT cooperative learning model assisted by Educaplay media is effective in improving student learning outcomes. The average N-Gain score was 0.72, which falls into the "high" category, confirming its effectiveness in enhancing learning outcomes. These findings demonstrate that the cooperative learning model of the TGT type when supported by Educaplay media, is effective in improving student academic performance. ABSTRAKAdapun tujuan penilitian berikut untuk mengetahui efektivitas model pembelajaran cooperative learning tipe TGT dengan bantuan media Educaplay untuk meningkatkan hasil belajar siswa kelas IX.8 di SMPN 3 Malang. Hal yang mendasari penelitian ini adalah pemilihan model pembelajaran yang terapkan pada materi yang bersifat teori seperti dalam materi Dampak Media Sosial menggunakan model pembelajaran konvensional yang kurang melibatkan keaktifan siswa sehingga dapat menyebabkan penurunan motivasi dan hasil belajar siswa. Penelitian ini menggunakan metode pre-eksperimental dengan rancangan satu kelompok yang diberikan pretest dan posttest. Sampel penelitian sejumlah 30 siswa kelas IX.8 di SMPN 3 Malang. Data yang didapatkan diujikan dengan menggunakan uji normalitas Shapiro-Wilk, uji-t paired sample test, dan uji N-Gain. Hasil uji normalitas pretest 0,125 dan posttest 0,086 berdistribusi normal. Hasil uji-t sebesar 0,000<0,05 mengindikasikan bahwa model pembelajaran kooperatif tipe TGT dengan bantuan media Educaplay efektif digunakan untuk meningkatkan hasil belajar siswa. Nilai rata-rata dari uji N-Gain sejumlah 0,72 yang berada dalam kategori tinggi berarti efektif dalam peningkatan hasil belajar siswa. Hal ini membuktikan bahwa model pembelajaran cooperative learning tipe TGT menggunakan media Educaplay efektif dalam meningkatkan hasil belajar.